CLINICAL FEATURES AND OUTCOMES MEASUREMENT OF CLOSE TIBIA FRACTURE OPEN REDUCTION INTERNAL FIXATION WITH FLUOROSCOPY (Vietnam Journal of Community Medicine, 2024)
Objective: Describing clinical features and outcomes of close tibia fracture ORIF (open reductioninternal fixation) at Vietduc University HospitalPatients and method: Prospective and retrospective studies 54 tibias close fractures were ORIFusing Carm from January 2020 to October 2022.Results: Mean ages 41,59 ± 12,89. 52/54 (96,3%) patients were good wound healing. The result of6 months postoperative was 57,5% excellent and 24,1% good. No patient has malalignment. Theexcellent result of Xray, according to Rasmusen, was higher in grades I, II, III, IV compared togrades V, VI (p
Keywords: Tibia fracture, C-arm, fluoroscopy.